Analysis of the dynamic correlation between chronic comorbidities and health shocks among middle-aged and older adults people in rural mountainous areas of southern Ningxia—from 14 years of follow-up panel data - Juan Yang; Juan Yang; Shan Liu; Shan Liu; Fei Li; Fei Li; Haodong Meng; Haodong Meng; Hui Qiao; Hui Qiao; Yongxin Xie; Yongxin Xie (Frontiers in Public Health)
BackgroundWith the acceleration of the aging process, the health shock on the middle-aged and older adults people has become a key issue that urgently needs to be solved. Health shock refers to the long-term fluctuating effect on the future level of family health welfare due to the uncertainty of the health status of family members in the short term. The occurrence of health shocks is related to many factors, among which chronic comorbidity is an important factor affecting the occurrence of health shocks in the middle-aged and older adults people. The purpose of this study was to explore the developmental trajectories and interactions of chronic comorbidities and health shocks in rural residents in the southern mountainous areas of Ningxia.MethodsOn the basis of health follow-up data from rural middle-aged and older adults people in Ningxia in 2009, 2015, 2019 and 2022, the dynamic associations between chronic comorbidities and health shocks in rural residents in mountainous areas of southern Ningxia were analyzed via the latent growth model (LGM) and cross-lagged model (CLM).ResultsThe unconditional latent growth model (ULGM) revealed that chronic comorbidities (χ2 = 26.807, p < 0.001) and health shocks (χ2 = 64.296, p < 0.001) are increasing in the 14-year period from 2009 to 2022. The parallel latent growth model (PLGM) revealed that the initial level of health shock had a significant positive predictive effect on both the initial level and the rate of change of chronic comorbidities. The change rate of health shocks had a significant positive predictive effect on the initial level of chronic comorbidities and a relatively significant negative predictive effect on the rate of change of chronic comorbidities. The initial level of chronic comorbidities had a significant positive predictive effect on the initial level of health shock and a significant negative predictive effect on the change rate of health shock. The change rate of chronic comorbidity has no significant predictive effect on the initial level and change rate of health shock. The results of the cross-lagged model (CLM) indicate a bidirectional causal association between chronic comorbidities and health shocks.ConclusionBased on a 14-year tracking data study, this research found that both chronic comorbidities and health shocks were on the rise, and there was a dynamic interaction and bidirectional causal relationship between the two, which could predict each other’s development trends. Based on the empirical results, it is recommended to strengthen the monitoring and management chronic comorbidities to reduce the risk of health shocks. Meanwhile, it is also necessary to closely monitor health shock events, and accordingly optimize the management strategies for chronic comorbidities, thereby reducing the incidence of health shocks among the middle-aged and older adults population, improving the quality of life and health, and promoting the realization of the goal of healthy aging.